2014
DOI: 10.1093/mnras/stu305
|View full text |Cite
|
Sign up to set email alerts
|

Herschel ★ -ATLAS: modelling the first strong gravitational lenses

Abstract: We have determined the mass-density radial profiles of the first five strong gravitational lens systems discovered by the Herschel Astrophysical Terahertz Large Area Survey (H-ATLAS). We present an enhancement of the semi-linear lens inversion method of Warren & Dye which allows simultaneous reconstruction of several different wavebands and apply this to dual-band imaging of the lenses acquired with the Hubble Space Telescope. The five systems analysed here have lens redshifts which span a range, 0.22 z 0.94. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
72
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 84 publications
(94 reference statements)
14
72
1
Order By: Relevance
“…In the intervening period, stars and dark matter become more mixed and thus better aligned with cosmic time. These results are consistent with strong lensing observations (e.g., Sluse et al 2012;Dye et al 2014, Rusu et al 2016. In particular, for galaxies that have stellar axis ratios falling within similar ranges as above, Gavazzi et al (2012) measured an rms scatter of 18…”
Section: Shape Of Luminous and Total Mattersupporting
confidence: 89%
“…In the intervening period, stars and dark matter become more mixed and thus better aligned with cosmic time. These results are consistent with strong lensing observations (e.g., Sluse et al 2012;Dye et al 2014, Rusu et al 2016. In particular, for galaxies that have stellar axis ratios falling within similar ranges as above, Gavazzi et al (2012) measured an rms scatter of 18…”
Section: Shape Of Luminous and Total Mattersupporting
confidence: 89%
“…The retrieved magnification are respectively 7.80 and 17.39 for the HST/WFC3 and ALMA observations. The first value is higher than (but consistent within 2.5σ with) the value tot ∼ 6.3 reported in Dye et al (2014, but the lens was modelled with a Singular Power Law Ellipsoid and resulted to be more spherical than what we find), the second is almost twice the value of µ 880 reported in Bussmann et al (2013), even though it is worth noticing that in that case the lens modeling method was a fully parametric one, with the reconstructed source modeled with a Sersic profile. Anyway, the high value of µ 1.3 is expected since the reconstructed source is compact and peaks close to the lens caustic.…”
Section: Modeling the Emission Of Sdp9supporting
confidence: 88%
“…Optical images of the foreground lens with the Keck telescope at g-and i-bands confirmed that their optical profiles are consistent with elliptical galaxies (Negrello et al 2010).Follow-up observations with the SMA at 880 m (Bussmann et al 2013) and with the Hubble Space Telescope at 1.1 and 1.6 micron confirmed them to be lensed galaxies. Dye et al (2014) modeled the lensed systems as being lensed by elliptical galaxies at redhift 0.6129 ± 0.00005 and 0.7932 ± 0.0012. The magnification factors µ are estimated to be 6.29 and 7.89 (8.8 and 10.9 according to Bussmann et al 2013) respectively for the two galaxies (see these values may be overestimated as they have been evaluated in a poorly sampled spectral region where contamination might enhance the signal in an unpredictable way.…”
Section: Introductionmentioning
confidence: 99%
“…We also do not show the centroid coordinates due to the uncertainty in the absolute astrometry, although the model uncertainty on the centroid is < 0.03 . Compared to the model of Dye et al (2014), we find a slightly steeper power law index and smaller Einstein radius, but the results are consistent within 2σ. However, we find a more elliptical mass distribution (b/a = 0.68 ± 0.05) compared to that of Dye et al (2014) (b/a = 0.88 ± 0.06).…”
Section: Lens Model Resultssupporting
confidence: 42%